2016
DOI: 10.1051/epjconf/201611402099
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic PIV measurement of boundary layer affected by DBD actuator

Abstract: Abstract. The effect of ionic wind generated by plasma actuator on developed boundary layer inside a narrow channel was investigated recently. Since the main investigated plane was parallel to the channel axis, the description of flow field was not evaluated credibly. This paper is dealing with cross-section planes downstream the actuator measured via 3D time-resolved PIV. The actuator position is in spanwise or in streamwise orientation so that ionic wind is blown in the same direction as the main flow or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The wire type of DBD actuator used for this study was developed and tested during long research along flat plate [5]. This type of actuator has proved that it can generate sufficient strong ionic wind to influence boundary layer and its plasma discharge is homogenous and constant in time.…”
Section: Actuator Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wire type of DBD actuator used for this study was developed and tested during long research along flat plate [5]. This type of actuator has proved that it can generate sufficient strong ionic wind to influence boundary layer and its plasma discharge is homogenous and constant in time.…”
Section: Actuator Descriptionmentioning
confidence: 99%
“…This regime seems to be very convenient for the purpose of active flow control utilization and it will be presented in the text further. The plasma actuator can generate necessary thrust in spanwise orientation (the same or opposite sense as channel flow) or in streamwise orientation, when the thrust is generated in perpendicular direction [5]. It has been shown that plasma actuation can stabilize or destabilize the boundary layer.…”
Section: Introductionmentioning
confidence: 99%